Disclosing the Potential of the SARP-Type Regulator PapR2 for the Activation of Antibiotic Gene Clusters in Streptomycetes - Krause, Janina; Handayani, Ira; Blin, Kai; Kulik, Andreas; Mast, Yvonne (Frontiers in Microbiology, 2020)
Streptomyces antibiotic regulatory protein (SARP) family regulators are well-known activators of antibiotic biosynthesis in streptomycetes. The respective genes occur in various types of antibiotic gene clusters encoding e.g. for polyketides, ribosomally and non-ribosomally synthesized peptides or ß-lactam antibiotics. We found that overexpression of the SARP-type regulator gene papR2 from Streptomyces pristinaespiralis in Streptomyces lividans leads to the activation of the silent undecylprodigiosin (Red) gene cluster. The activation happens upon the inducing function of PapR2, which takes over the regulatory role of RedD, the latter of which is the intrinsic SARP regulator of Red biosynthesis in S. lividans. Due to the broad abundance of SARP genes in different antibiotic gene clusters of various actinomycetes and the uniform activating principle of the encoded regulators, we suggest that this type of regulator is especially well suited to be used as an initiator of antibiotic biosynthesis in actinomycetes. Here, we report on a SARP-guided strategy to activate antibiotic gene clusters. As a proof of principle, we present the PapR2-driven activation of the amicetin/plicacetin gene cluster in the novel Indonesian strain isolate Streptomyces sp. SHP22-7.